Chemical sensing in two dimensional porous covalent organic nanosheets1. Issue 7 (15th July 2015) - Das, Gobinda; Biswal, Bishnu P.; Kandambeth, Sharath; Venkatesh, V.; Kaur, Gagandeep; Addicoat, Matthew; Heine, Thomas; Verma, Sandeep; Banerjee, Rahul
<x xml:space="preserve">Abstract</x> Covalent organic nanosheets (CONs) were synthesised from imide functionalised COFs. TfpBDH-CONs exhibit a "turn-on" detection capability for 2, 4, 6-trinitrophenol in the solid state, but show a "turn-off" detection in the dispersion state.